APLICATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES FOR 4TH GRADE STUDENTS OF SDN NO. 48 INPRES GALUNG UTARA BANGGAE DISTRICT MAJENE REGENCY - Nurhidayah Nurhidayah; Sayidiman Sayidiman; Nurhaedah Nurhaedah (International Journal of Elementary School Teacher, 2022)
The problem behind this research is the low learning outcomes of students in learning Mathematics for class IV SDN No. 48 Inpres Galung Utara, Banggae District, Majene Regency. This study aims to describe the application of the Problem Based Learning model to improve mathematics learning outcomes for fourth grade students of SDN No. 48 Inpres Galung Utara, Banggae District, Majene Regency. The approach used is a qualitative approach and the type of classroom action research (CAR) which consists of 2 cycles, each cycle consisting of 2 meetings with the stages of activities in the form of planning, implementing, observing, and reflecting. The focus of this research is the application of the Problem Based Learning model and student learning outcomes. The research subjects are teachers and fourth grade students at SDN No. 48 Inpres Galung Utara, Banggae District, Majene Regency. In the even semester of the 2022/2023 academic year, there are 18 students. Collecting data using the format of observation, tests and documentation. The data analysis used is qualitative. The results showed that there was an increase in learning both in teacher and student activities and student learning outcomes. The results of this study are teacher teaching activities and student learning activities have increased, in the first cycle the second meeting is in the sufficient category while in the second cycle the second meeting is in the good category. Student learning outcomes in cycle I meeting II are in the high category but student learning outcomes in Mathematics learning have not been completed classically, while in cycle II meeting II the category is very high, student learning outcomes have increased and have been completed classically. The conclusion of this study is that the application of the Problem Based Learning model in learning Mathematics can improve the learning outcomes of fourth grade students at SDN No. 48 Inpres Galung Utara, Banggae district Majene Regency.